Influence of a glide path on the dentinal crack formation of ProTaper Next system - Sevinç Aktemur Türker; Emel Uzunoğlu (Korean Academy of Conservative Dentistry, 2015)
Objectives The aim was to evaluate dentinal crack formation after root canal preparation with ProTaper Next system (PTN) with and without a glide path. Materials and Methods Forty-five mesial roots of mandibular first molars were selected. Fifteen teeth were left unprepared and served as controls. The experimental groups consist of mesiobuccal and mesiolingual root canals of remaining 30 teeth, which were divided into 2 groups (n = 15): Group PG/PTN, glide path was created with ProGlider (PG) and then canals were shaped with PTN system; Group PTN, glide path was not prepared and canals were shaped with PTN system only. All roots were sectioned perpendicular to the long axis at 1, 2, 3, 4, 6, and 8 mm from the apex, and the sections were observed under a stereomicroscope. The presence/absence of cracks was recorded. Data were analyzed with chi-square tests with Yates correction. Results There were no significant differences in crack formation between the PTN with and without glide path preparation. The incidence of cracks observed in PG/PTN and PTN groups was 17.8% and 28.9%, respectively. Conclusions The creation of a glide path with ProGlider before ProTaper Next rotary system did not influence dentinal crack formation in root canals.